2006
DOI: 10.1007/s11434-006-2189-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of high-road-side pine tree leaves in Beijing and their environmental significance

Abstract: This is a report on magnetic properties of highroad-side tree (Pinus pumila Regel) leaves collected along an expressway linking Beijing City and the Capital International Airport and further focus on their environmental contributions. A series of rock magnetic experiments show that the primary magnetic mineral of leaf samples was identified to be magnetite, in the pseudo-single domain (PSD) grain size range 0.2-5.0 μm. On the other hand, magnetite concentration and grain size in leaves are ascertained to decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 31 publications
6
33
0
1
Order By: Relevance
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental magnetism has become one of the main focuses of current research in pollution history reconstruction, monitoring the present environmental pollution, and tracing and separating the sources of pollution. The atmosphere [18][19][20][21], street dustfall [22][23][24][25], soil [1][2][3][4][5][6][7][8][9][10][11], sediment [12][13][14], leaves [26][27][28][29] and tree rings [30] are usually used as the research targets. Analysis is developed from a single Wang B, et al Chin Sci Bull January (2013) Vol.58 No.3 385 pollution source to multiple pollution sources and multivariate data analysis, and in some studies semi-quantitative models are created.…”
mentioning
confidence: 99%
“…Zhu et al [31] investigated the scaling of directed dynamical small-world networks with random responses. Some other noteworthy results can be seen in [32][33][34][35][36][37][38][39][40].…”
mentioning
confidence: 78%